Prefácios e notas do tradutor: tensão e acolhimento na relação com o outro - Rodrigues, Cristina Carneiro [UNESP] (My University, 2010)
The purpose of this paper is to examine the paratexts, mainly prefaces and notes, written by translators on writings of foreigners' travels in Brazil, with the purpose of evidencing which perspective guided their translations, if the perspective of the foreign author is adopted or if it is that of the domestic reader. The works examined were published by the Brazilian publishing house Companhia Editora Nacional in the Brasiliana Colllection. Most of the translators adopted a welcoming discourse to the author in their prefaces, but their prefaces, translations and notes reveal a certain tension between what they stated and what was effectively done, with moments of rupture in which the author's meanings are questioned and even denied. According to my analysis, this happens because the several forces acting on the translation, the author, the translator and the text to be translated, the languages involved, the reader are not working linearly, but in constant tension. As a result, different perspectives are adopted in different translations, but in the same translation there are moments in which the foreign pole is privileged and moments in which the domestic pole emerges.

Este trabalho tem como objetivo examinar os paratextos, especialmente prefácios e notas, escritos por tradutores de relatos de viagem de estrangeiros pelo Brasil, com o propósito de evidenciar qual foi a perspectiva que orientou essas traduções, se a perspectiva privilegiada é a do autor estrangeiro ou a do leitor. As obras examinadas foram publicadas pela Companhia Editora Nacional na Coleção Brasiliana. A maior parte dos tradutores constrói o discurso de acolhimento ao autor nos prefácios, mas as traduções, os prefácios e as notas revelam certa tensão entre o declarado e o efetivamente realizado, havendo momentos de ruptura em que os sentidos do autor estrangeiro são questionados ou até mesmo negados. Em minha análise, isso ocorre porque as várias forças que atuam sobre o traduzir, como o autor, o tradutor, o texto a ser traduzido, as línguas envolvidas, o leitor, não agem linearmente, estão em constante tensão. Como resultado, não só há perspectivas diferentes adotadas em diferentes traduções, como também em uma mesma tradução há momento em que o pólo estrangeiro é privilegiado e momentos em que o pólo doméstico aflora.
Prefaces and translator's notes: tension and welcoming in the relationship with the other
Keywords: Relatos de viagem; Paratexto; História da Tradução; Companhia Editora Nacional